A Memory-Efficient Algorithm for Conservative Cuts in Disjoint Bilinear Programming - Xiaosong Ding; Chao Liu; Jun Ma; Xi Chen; Quing Sun (Acta Universitatis Sapientiae: Informatica)
This paper presents a memory-efficient approach to the combinatorial challenges associated with the process in search of conservative cuts for degeneracy removal in disjoint bilinear programming. Drawing inspiration from Pascal’s Triangle, the new randomized approach surpasses its predecessor from the perspective of memory, and thereby enables the possibility of its application to disjoint bilinear models with high degrees of degeneracy in imprecise decision analysis on a PC. Numerical reports are provided to validate its computational performance.